Development of containerized pipelines for the reproducible analysis of amplicon-, shotgun metagenomic- and metatranscriptomic data. - Madzime, Ruvarashe Joylyne (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.